A6.7 Evaluation of porphyromonas gingivalis serology in rheumatic and non-rheumatic inflammatory disease. (31st January 2014) - Rinaudo-Gaujous, M; Moreau, A; Blasco-Baque, V; Roblin, X; Genin, C; Thomas, T; Paul, S; Marotte, H
Abstract : Objectives: Porphyromonas gingivalis ( P. gingivalis ) interest for RA development disease is growing fast since it is the only bacteria able to citrullinate peptides and may induce autoimmune response through development of ACPA. However, few studies have reported its presence in others inflammatory diseases. The aim of this study is to evaluate the specificity of P. gingivalis and Prevotella intermedia ( P. intermedia ) serology in patients with rheumatic diseases including rheumatoid arthritis (RA) and spondylarthritis (SA) compared to controls (healthy subjects or patients with inflammatory bowel disease (IBD)). Methods: We enrolled in this study 79 RA patients, 56 SA patients and 39 IBD patients requiring infliximab therapy, as well as 30 healthy controls. Anti- P. intermedia antibodies and anti- P. gingivalis LPS specific and whole extract antibodies were determined by ELISA. Specificity of these antibodies was evaluated by the search for antibodies against a commensal bacterium of the intestinal tract: Escherichia Coli (E. coli). Results: Anti- P. gingivalis antibody titers determined by LPS and whole extract were well correlated together (P < 0.0001) as well as antibody titers against the two oral bacteria ( P. gingivalis and P. intermedia ) (P < 0.0001). By using LPS from E. coli, no cross reaction was observed as high anti- P. gingivalis antibody titers were negative for anti- E. coli antibody and vice versa. Anti-P. gingivalis antibodies titers were higher in RA and SA patients than in healthy subjects (P < 0.0001) or in IBD patients (P< 0.0001). Moreover, there was a trend for higher titers in RA patients than in SA patients (Fig 1A). Same results were found with anti- P. intermedia antibody titers which were higher in RA and SA patients than in healthy controls (P < 0.0001) or IBD patients (P < 0.0001) (Fig 1B). Conclusions: P. gingivalis and P. intermedia are oral bacteria having an important role in rheumatic diseases, especially in RA, compared to another inflammatory disease as shown by higher titers of antibodies found in both RA and SA.